THE ROLE OF ADVISORY SERVICES IN THE CREATION OF INVESTMENT ACTIVITY OF PRIVATE FARMS - Kalinowski, Sławomir; Kiełbasa, Barbara (Acta Scientiarum Polonorum. Oeconomia, 2010)
Investments are a propeller of activity in every company or a farm. Investments decision is a high risk of both small (private) and large farms. Nowadays, facing the implementation of new requirements in agricultural production, it is sometimes necessary to invest a lot of money in the modernization of the farm. In Malopolska province, where research have been conducted, farmers often choose the replacement investments, having the character of productive investments. Due to the specific conditions of production, often resulting in inefficiency and its unavailability, farmers rarely invest in development of their farm. The paper presents brief descriptions of the sample of 849 households, an assessment of investments activities and plans for the future, and also analyze of the source of getting information to farmers in the field of investment possibilities.